Pengaruh Kualitas Konten, Brand Image, dan Brand Trust Terhadap Efektivitas Promosi Produk di Akun Instagram Kriya Sriwijaya - Anjani Sanjani; Leti Karmila (Buana Komunikasi (Jurnal Penelitian dan Studi Ilmu Komunikasi), 2025)
The increase in internet penetration in Indonesia, which reached 79.5% in 2024, opened opportunities for the use of Instagram as a digital marketing platform. Kriya Sriwijaya, as a center for education and the development of South Sumatra’s crafts, used this platform to expand its market reach and promote local cultural products. This study aimed to analyze the influence of content quality, brand image, and brand trust on the effectiveness of product promotion on the Kriya Sriwijaya Instagram account, both partially and simultaneously. The research employed an explanatory quantitative method. The results showed that content quality and brand image had significant effects on promotional effectiveness, with p-values of 0.00 < 0.05. Meanwhile, brand trust had no significant effect, indicated by a p-value of 0.120 > 0.05. Simultaneously, the three variables explained 74.1% of promotional effectiveness. These findings indicated that content quality and brand image reinforced brand perception and enhanced promotional effectiveness. Keywords: Content Quality, Brand Image, Brand Trust, Promotional Effectiveness, Instagram